MEMPERKUAT BUDAYA ORGANISASI MELALUI PENINGKATAN VALUE PADA YAYASAN SAHABAT YATIM : MEMPERKUAT BUDAYA ORGANISASI MELALUI PENINGKATAN VALUE PADA YAYASAN SAHABAT YATIM - Febrian, Wenny Desty Febrian; Solihin, Agung (Andhara, 2023)
Abstract This Community Service aims to provide knowledge and insight about the development of human resources through an Organizational Culture that produces value for the superiority of these human resources so that they are able to compete. The purpose of the Organizational Culture is to provide counseling about the scope through strengthening the values ​​of organizational culture at the Tahfidz Maskanul Huffadz Foundation in South Tangerang so that it has the character and attractiveness of organizational behavior in order to develop a culture of achievement, change mindsets and maintain trust in the organization. Each organization, including the Sahabat Yatim Foundation, has a different way of carrying out an activity and solving the problems it faces to achieve certain goals, so it can be said that the culture of each country is different. In a certain country there are also certain groups that have different cultures, that is what is called a sub-culture (sub-culture). Keyword : Organizational Culture, Value